Evaluation of professional nursing practice environments in primary health care - de Lima Trindade, Letícia; Guerreiro, Bruna de Campos; de Oliveira, Sandra Mara Soares; Ventura-Silva, João Miguel Almeida; Rostirolla, Leticia; Zuge, Samuel Spiegelberg; Ribeiro, Olga Maria Pimenta Lopes (Frontiers in Public Health, 2025)
ObjectiveAnalyzing the environments of professional nursing practice in Primary Health Care in a municipality in the west of the state of Santa Catarina.MethodA quantitative, explanatory, cross-sectional study was carried out in 24 Primary Care health units. A total of 159 nursing professionals took part and answered a questionnaire on personal and professional characteristics and the Nursing Professional Practice Evaluation Scale/SEE-Nursing Practice, comprised of Structure, Process, and Outcome sub-scales. The data was subjected to descriptive and inferential analysis.ResultsThere were positive evaluations for people management and leadership in the Structure dimension. Technicians and nursing assistants had positive evaluations of the organization and sustainability of practice. In Process, collaboration and teamwork stood out, and strategies to guarantee the quality of care. In the Outcome dimension, there was a relationship between gender and systematic evaluation of care, with higher scores among women.ConclusionA positive evaluation of professional nursing practice environments in Primary Care contributes to the effective management of people, materials, and care processes, reflecting on the quality of nursing practice and access to healthcare.